MECHANISM OF HYDROGENOLYSIS REACTION OF ORCHOLOGICAL COMPOUNDS ON HETEROGENEOUS CATALYSTS - Білокопитов, Ю. В.; Іванов, С. В.; Ледовських, В. М.; Сергунов, Ю. О. (Proceedings of National Aviation University (archive), 2021)
The mechanism of hydrogenolysis of benzene chlorine derivatives has been studied. It is shown that the reaction occurs in the chemisorbed state, the limiting stage is the dissociative chemisorption of chlorobenzenes. It is proved that the process of exchange of several chlorine atoms in polychlorobenzenes for hydrogen is carried out sequentially.